[R]Evolution in Foreign Language Teaching - Giving Voice to International Teachers - Hurst, Nicholas; Bekteshi, Edita (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2019)
In the last few decades, foreign language instruction in Higher Education institutions (HEIs) has changed from its traditional teaching mode (transmission of knowledge) to a more modern teaching mode (development of competences); however, this change has been implemented in disparate ways in different contexts around the globe. In terms of foreign language teaching (FLT) methodology in an international context, these changes may be seen to represent an Evolution, in certain contexts or a Revolution, in others. This study aims to give voice to FLT practitioners from just such different educational settings: professionals who are concerned with developing better FLT methodology. How difficult are the ideas of [R]evolution in education to describe? How easy or how hard is to put the new educative practices in place? The conclusion is that nowadays teachers’ interpretations of what is ‘modern’ is based on modifying students’ learning behaviours through the use of effective, cognitive methods based on social-cultural interaction. The paper suggests that further methodological change has the potential to help make significant progress towards strategic development in 21st century society, particularly with issues related to interculturality, global citizenship education and the implementation of glocally (Global and Local) appropriate approaches to FL teaching and learning.